46,XY/45,X mosaicism in an amniotic fluid cell culture: suppression of abnormal cell line after subcultivation. - Hasholt, L (1979)
An abnormal cell population, 45,X, appeared in 3 of 4 cell lines established from an amniotic fluid specimen obtained from a normal mid-trimester pregnancy. Two of the cell lines were subjected to repeated chromosome analyses until VII passage. The abnormal cells were suppressed after repeated trypsinisations; simultaneously, fibroblast-like cells outgrew the cultures, which were previously predominated by epithelial-like cells. Polyploidy was found in 0 to 12% of the cells, the highest level existing in the early passages. The question of whether chromosomally abnormal cells present in primary cultures and the early subcultures reflect the karyotype of the fetus is discussed.